SPECTROSCOPY OF VIRGINIDS - Galazutdinov, G. A. (Одеські астрономічні публікації, 2017)
Spectroscopic observations of 10 W Vir type stars were obtained at 6-m telescope by using the Echelle spectrometers ES-PAC and Lynx. By using the method of model atmospheres the chemical composition was determined for V 351 Cep, BL Her, TX Del. Positional measurements of the lines formed in different layers were obtained for V 351 Cep, Preliminary conclusions are the following: the sample of the observed virginids is not homogeneous. The objects of solar chemical composition were discovered for which the usage of the dependence "period-luminosity" (obtained for the halo cepheids) leads to the anomalous low luminosity values. These stars are not representatives of the Il-nd type population. Few short-period virginids have secondaries seen in variability of the radial velocities. From the whole set of parameters, we may not classify these objects also as classical disk cepheids, because the light curve does not correspond to the dependence "period-phase curve" for classical cepheids. Possible explanation of the observed properties of some short period virginids is a hypothesis of their possible binarity. Or they belong to a class of "anomalous cepheids" which we propose to discuss as a result of the coalescence of the components in a close binary system.